2016
DOI: 10.1515/bioeth-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from brown seaweed using non-conventional yeasts

Abstract: Abstract:The use of macroalgae (seaweed) as a potential source of biofuels has attracted considerable worldwide interest. Since brown algae, especially the giant kelp, grow very rapidly and contain considerable amounts of polysaccharides, coupled with low lignin content, they represent attractive candidates for bioconversion to ethanol through yeast fermentation processes. In the current study, powdered dried seaweeds (Ascophylum nodosum and Laminaria digitata) were pre-treated with dilute sulphuric acid and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…On the other hand, Solarin et al [23] found that the carbohydrates content in Sargassum hystrix was (58.72%). Obata et al [24] studied other examples of the brown macroalgae (Ascophylum nodosum and Laminaria digitate), they found that carbohydrates content was (57.84 and 64.47%) respectively which supported our results that the brown macroalgae have high carbohydrates content. Also, Jang et al [25] reported another study on Laminaria japonica which considered an example of brown algae, he found that the carbohydrates content (54.5%).…”
Section: The Composition Of the Collected Algal Substratesupporting
confidence: 89%
“…On the other hand, Solarin et al [23] found that the carbohydrates content in Sargassum hystrix was (58.72%). Obata et al [24] studied other examples of the brown macroalgae (Ascophylum nodosum and Laminaria digitate), they found that carbohydrates content was (57.84 and 64.47%) respectively which supported our results that the brown macroalgae have high carbohydrates content. Also, Jang et al [25] reported another study on Laminaria japonica which considered an example of brown algae, he found that the carbohydrates content (54.5%).…”
Section: The Composition Of the Collected Algal Substratesupporting
confidence: 89%
“…Nowadays, hydrothermal treatment with diluted acids at concentrations between 0.2% and 2.5% (w/w) or alkali at temperatures ranging between 130 and 210°C is the most widely used pretreatment method (Jiang et al, ; Lee et al, ). Jiang et al () paid particular attention to the fact that in some studies treatment with dilute acid (<5%) was considered as “pretreatment,” whereas in others it was called “acid hydrolysis.” Acid or alkali hydrolysis is generally followed by enzymatic treatments (please see Table ; e.g., Borines et al, ; Jiang et al, ; Khan & Hussain, ; Korzen et al, ; Obata et al, ). The first method has many advantages such as simplicity, speed, and relatively low costs.…”
Section: Technologies Converting Algal Biomass To Energymentioning
confidence: 99%
“…Jiang et al (2016) paid particular attention to the fact that in some studies treatment with dilute acid (<5%) was considered as "pretreatment," whereas in others it was called "acid hydrolysis." Acid or alkali hydrolysis is generally followed by enzymatic treatments (please see Table 2; e.g., Borines et al, 2013;Jiang et al, 2016;Khan & Hussain, 2015;Korzen et al, 2015;Obata et al, 2016). The first method has many advantages such as simplicity, speed, and relatively low costs.…”
Section: Bioethanol Productionmentioning
confidence: 99%
See 2 more Smart Citations